SARS-COV-2 INFECTION: CARDIAL AND MULTI-ORGAN INVOLVEMENT - Furnadziski, Aleksandar; Mitevski, Goran; Nikolovski, Robert; Nikolov, Igor; Plasheski, Tosho; Georgiev, Antonio (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2022)
SARS-COV-2 is a single-strain RNA virus that attacks primarily the respiratory system. The second most commonly affected system is the cardiovascular. Often it attacks multiple organ systems causing multi-organ failure. Atrial fibrillation (AF) is the most common sustained supraventricular arrhythmia in acute settings of COVID-19 infection and is associated to more complications and mortality rates. The presence of AF in patients with COVID-19 pneumonia should be managed with increased attention to prevent adverse outcomes. COVID-19 may be a cause of multiple organ damage in some infected patients.
Keywords: SARS-CoV-2; atrial fibrillation; hypothyroidism; rhabdomyolysis; kidney damage